Creative Thinking Processes in High School Visual A - Marquez, Josemarie Rose S.; Koo, Grace S.; Lusung-Oyzon, Maria Vanessa (Philippine Journal of Education Studies (formerly the Education Quarterly), 2025)
Recent research on creative thinking in education has modeled cognitive, affective, and contextual factors, but little focuses on digitally-enhanced environments. This study explores the use of new media technology in High School Visual Arts classes through a descriptive case study. Twenty-six students were interviewed and their artistic activities were documented in a Creative Process Report Diary. Thematic analysis revealed that new media technology influences the creative thinking process in several ways: its functionality facilitates creative thinking by reducing cognitive load and enabling diverse ideas, while non-functional tools hinder creativity; the psychological meaning associated with new media technology, characterized by positive effects and meanings, enhances task motivation and creative effort; and its empowering nature supports less skilled students in improving their creative output. Furthermore, students' engagement with technology varies depending on their skills, experiences, and personality, showcasing advanced creativity-relevant processes. Although the stages of creative thinking remain consistent, new media technology reshapes the experiences within these stages, enabling more efficient information gathering and faster creation.            The study concludes that new media technology influences high school students' creative thinking through the interaction between the individual, the surrounding environment, and the goal of creation, enhancing their overall creative experience.